Magnetic configurations in nanostructured Co2MnGa thin film elements. (17th August 2015) - Finizio, S; Kronenberg, A; Vafaee, M; Foerster, M; Litzius, K; Lucia, A de; Menteş, T O; Aballe, L; Krüger, B; Jourdan, M; Kläui, M
Abstract: The magnetic configuration of nanostructured elements fabricated from thin films of the Heusler compound Co2 MnGa was determined by high-resolution x-ray magnetic microscopy, and the magnetic properties of continuous Co2 MnGa thin films were determined by magnetometry measurements. A four-fold magnetic anisotropy with an anisotropy constant of kJ m −3 was deduced, and x-ray microscopy measurements have shown that the nanostructured Co2 MnGa elements exhibit reproducible magnetic states dominated by shape anisotropy, with a minor contribution from the magneto-crystalline anisotropy, showing that the spin structure can be tailored by judiciously choosing the geometry.